Discovery of a red backsplash galaxy candidate near M81. Issue 3 (1st February 2023) - Casey, Kirsten J; Greco, Johnny P; Peter, Annika H G; Davis, A Bianca
ABSTRACT: Understanding quenching mechanisms in low-mass galaxies is essential for understanding galaxy evolution overall. In particular, isolated galaxies are important tools to help disentangle the complex internal and external processes that impact star formation. Comparisons between quenched field and satellite galaxies in the low-mass regime offer a substantial opportunity for discovery, although very few quenched galaxies with masses below $M_{\star }\, \sim \, 10^{9} {\rm M}_{\odot }$ are known outside the virial radius, R vir, of any host halo. Importantly, simulations and observations suggest that an in-between population of backsplash galaxies also exists that may complement interpretations of environmental quenching. Backsplash galaxies – like field galaxies – reside outside the virial radius of a host halo, but their star formation can be deeply impacted by previous interactions with more massive systems. In this paper, we report the concurrent discovery of a low-mass ($M_{\star }\, \sim \, 10^{7} {\rm M}_{\odot }$ ) quenched galaxy approximately 1 R vir in projection from the M81 group. We use surface brightness fluctuations (SBF) to investigate the possibility that the new galaxy, dw0910+7326 (nicknamed Blobby), is a backsplash galaxy or a more distant field galaxy. The measured SBF distance of $3.21\substack{+0.15 +0.41 \\-0.15 -0.36}$ Mpc indicates that Blobby likely lies in the range 1.0 < R / R vir < 2.7 outside the combined M81–M82 system. Given its distance and quiescence, Blobby is a good candidate for a backsplash galaxy and could provide hints about the formation and evolution of these interesting objects.